Role of automatic, conscious, and unconscious thought processes in complex decision making - Levačić, Draženka; Pandžić, Mario; Glavaš, Dragan (Primenjena psihologija)
A complex decision is any decision that includes choosing among options with numerous describing attributes. Certain decisions are fast, often guided with automatic thought processes, while other decisions are made with careful examination of all the factors. The aim of this research was to investigate the effect of automatic, conscious and unconscious thought processes in the context of decision making. Participants were psychology students aged between 19 to 28 years. The first experiment investigated the role of these three different thought processes on choosing a subjectively best apartment option and take-the-best (TTB) heuristic apartment option. The second experiment investigated metacognitive aspects of decision making, precisely to determine the differences in feeling of rightness (FOR) as well as the tendency to change the decision about the chosen apartment, depending on the activated thought processes. Different thought processes determined the choice of the subjectively best option. Participants chose the subjectively best option in the conscious thought condition more often than in the automatic or unconscious thought condition. However, there was no difference between conditions in choosing the TTB heuristic option. No difference was found between the automatic and unconscious thought condition concerning the metacognitive assessment of feeling of rightness, while the same increased equally in participants of both conditions after they were subsequently included in the conscious thought condition. The tendency to change responses after engaging in a conscious thought condition also did not depend on the initial condition. The study provided support for the importance of conscious thought processes in complex decision making present in everyday functioning and regardless of the field of human expertise.